What is changing in the treatment of acute coronary syndrome in the Russian Federation? - S. A. Boytsov; B. G. Alekyan; R. M. Shakhnovich; V. I. Ganyukov (Рациональная фармакотерапия в кардиологии)
The work of the national network of vascular centers of the Russian Federation (RF), based on the Clinical recommendations of the Russian Society of Cardiology and the procedure for providing medical care to patients with cardiovascular diseases, has led to significant positive results in the treatment of patients with acute coronary syndrome (ACS) in the country, although a number of targets have not yet been reached. The purpose of the publication is to demonstrate the trend in therapeutic approaches to the management of patients with ACS in 2020-2022. in Russia and analysis of their effectiveness. Quantitative and qualitative indicators of the treatment of patients with ACS for the presented analysis were obtained on the basis of monitoring data from the Russian Ministry of Health for 2018-2021. presented: Monitoring of measures to reduce mortality from coronary heart disease, letters of the Ministry of Health of Russia dated March 13, 2015 No. 17-6 / 10 / 1-177 and dated July 24, 2015 No. 17-9 / 10 / 2-4128, within which data collection carried out monthly, on the portal of the Federal State Budgetary Institution "TsNIIOIZ" of the Ministry of Health of Russia - Automated system for monitoring medical statistics and the register REGION-IM (Russian Register of Acute Myocardial Infarction) - a multicenter prospective observational cohort study for 2020-2022, organized by the Federal State Budgetary Institution "National Medical Research Center of Cardiology named after Academician E.I. Chazov" of the Ministry of Health of Russia. In Russia with a diagnosis of ACS in 2020 and 2021 403,931 and 397,930 patients were hospitalized, respectively. The decrease in the number of patients diagnosed with ACS admitted to Russian hospitals by 22.32% was mainly due to a significant decrease in hospital admissions of patients diagnosed with non-ST elevation ACS (non-STE-ACS) (by 29.03%). At the same time, the admission of patients with ST elevation myocardial infarction (STEMI) decreased only by 6.02%. Compared to 2018-2019, in 2020-2022. increased mortality in primary percutaneous coronary intervention (PCI) (by 9.6%) and in the general STEMI group (by 12.3%); significantly increased mortality both in the general group of NSTE-ACS (by 48%) and during PCI for patients with non-STE-ACS (by 28.6%); there was an increase in the average annual number of primary PCI (by 12.6%); an absolute and relative increase in the number of PCI in non-STE-ACS was revealed (by 2.7 and 37.1%, respectively). In the country's hospitals, by the time of discharge, 95% of patients receive statins, beta-blockers – 87%, ACE inhibitors – 80%, acetylsalicylic acid – 82%, P2Y12 inhibitors – 98% of patients, regardless of the type of ACS. In Russia in 2020-2022 unfavorable tendencies in the provision of care to patients with ACS include: increased mortality in primary PCI and in the general STEMI group; increased mortality both in the general group of non-STE-ACS and during PCI for patients with non-STE-ACS. The positive results of the work of the national network of vascular centers include: absolute, relative and estimated increase in the number of primary PCI; absolute and relative increase in the number of PCI in non-STE-ACS; a high level of prescribing drugs with a proven positive effect on the prognosis.